Corrosion of Copper-coupled Steel in Open Recirculating Cooling Water System - Omar, Muhammad Ikmal (IRC, 2018)
Corrosion in cooling water system pipelines brings a major concern towards many industries processing plants. Widely used of steel and copper causes galvanic corrosion to occur within the system. To overcome the corrosion issue, most industries have used inorganic chemical like chromate as corrosion inhibitors. Therefore, the aims of this project are to study the corrosion rate of steel when it is galvanically in contact with copper and to study the performance of organic corrosion inhibitors (CI) in controlling the corrosion process. Mini flow loop experiment is set up as per in ASTM D688 as the testing method to acquire reliable results for this project. Simulated cooling water (SCW) is prepared in the laboratory at pH 8.0 with room temperature to match the composition of cooling water in the plant. Two parameters are tested in these experiments which are low velocity condition of 0.25 m/s and high velocity condition of 1.1 m/s. The average corrosion rate for non-coupled steel experiment in low velocity of uninhibited SCW is 2.74 mmpy while in high velocity is 1.17 mmpy. When steel is coupled with copper alloy in low velocity condition, the highest corrosion rate of the steel in uninhibited SCW is 2.78 mmpy, whereas the lowest corrosion rate is 0.89 mmpy in SCW with the addition of 16% of tobacco extract water solution. In high velocity condition, the highest corrosion rate of the steel is 3.97 mmpy in uninhibited SCW, whereas the lowest corrosion rate is 0.78 mmpy in SCW with the addition of tobacco solution. The copper alloy shows a small value of corrosion rate in low and high velocity – 0.35 mmpy and 0.41 mmpy in uninhibited SCW. In the presence of CI, the corrosion rate of copper reduced to 0.03 mmpy in low velocity and 0.04 mmpy in high velocity. Based on the results, it shows that the corrosion rate of steel increased dramatically when coupled with copper both in low and high velocity. The performance of CI is efficient in high velocity condition which achieved the inhibition efficiency (IE) of 72.03% compared to low velocity condition which gives 67.8% of IE.